Representasi Pesan Ta’awun Dalam Film Kukira Kau Rumah Karya Umay Shahab: merepresentasikan pesan ta'awun atau tolong-menolong dalam film KuKira Kau Rumah - Annisa Dea Syifani; Suslina Sanjaya; Ade Nur Istiani (Palakka : Media and Islamic Communication, 2025)
This study examines the representation of ta'awun, or long-helping, in the film Kukira Kau Rumah by Umay Shahab through Charles Sanders Peirce's semiotic analysis. This film was chosen because it raises the issue of mental health and social relationships that are full of values ​​of empathy and caring. The aim of this study is to find out how the value of ta'awun is represented through visual and verbal signs that appear in various film scenes. The method used is a descriptive qualitative method with semiotic analysis techniques, which include three main elements: icons, indices, and symbols. The results of the study show that icons appear in facial expressions, gestures, and actions of characters that represent empathy and support. The index is seen through the character's actions, which arise from a sense of care and a desire to help. The symbol reflects a broader moral meaning as a form of mutual assistance in emotional and social aspects. As a form of novelty, this study shows that the representation of ta'awun in films extends beyond concrete assistance to include affective dimensions such as empathy, attention, and psychological strengthening, thereby enriching the perspective of Islamic communication studies through film media. In conclusion, the film Kukira Kau Rumah not only explores psychological issues but also emphasizes the importance of human values and empathy between individuals as a tangible manifestation of ta'awun in everyday life.